Sensitivity Assessment of the Seismic Response of a Masonry Palace via Non-Linear Static Analysis: A Case Study in L’Aquila (Italy) - Ilaria Capanna; Angelo Aloisio; Franco Di Fabio; Massimo Fragiacomo (Infrastructures, 2021)
The city of L’Aquila (Italy) includes a significant amount of masonry palaces erected from the middle of the 13th century up to the first half of the 20th century. This paper focuses on the seismic response of a masonry palace built during the first half of the 20th century and characterized by regularity in plan and elevation. The authors investigate the seismic response by varying a suite of modelling parameters that express the actual scatter of the mechanical properties typical of the masonry palaces erected in L’Aquila. The authors discuss the seismic performance exhibited by this building during the 2009 earthquake. Then, they assess the sensitivity of the selected building’s seismic performance via non-linear static analysis to the mechanical properties of masonry, the in-plane stiffness of the floors, and the mechanical resistance of the spandrels. The parametric analysis shows that the three variables markedly affect the shear resistance, the ultimate displacement, and the behavior factors. The fragility functions were then estimated from the results of non-linear static analysis. A significant scatter of the probability of collapse for the considered limit states reveals the limitations of typological approaches for masonry palaces.